2006
DOI: 10.1021/jf058171g
|View full text |Cite
|
Sign up to set email alerts
|

Red Grapefruit Positively Influences Serum Triglyceride Level in Patients Suffering from Coronary Atherosclerosis:  Studies in Vitro and in Humans

Abstract: The contents of the bioactive compounds in red and blond grapefruits and their influence on humans suffering from hypertriglyceridemia were studied. It was found that red grapefruit has a higher content of bioactive compounds and a higher antioxidant potential than blond grapefruit, determined by oxygen radical scavenging capacity, 1,1-diphenyl-2-picrylhydrazyl, carotenoid bleaching, and Folin-Ciocalteu assays. Fifty-seven hyperlipidemic patients, ages 39-72 years, after coronary bypass surgery, recruited from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 31 publications
(45 reference statements)
5
61
1
Order By: Relevance
“…Similar studies conducted on human subjects have shown that red grapefruit significantly lowers serum total cholesterol, low-density lipoprotein cholesterol and triglycerides in patients with coronary atherosclerosis [9]. A recent study by Fujioka et al [10] reported that consumption of whole grapefruit or GFJ is associated with significant weight loss and improved insulin resistance in patients with metabolic syndrome, compared to placebo.…”
Section: Introductionmentioning
confidence: 78%
“…Similar studies conducted on human subjects have shown that red grapefruit significantly lowers serum total cholesterol, low-density lipoprotein cholesterol and triglycerides in patients with coronary atherosclerosis [9]. A recent study by Fujioka et al [10] reported that consumption of whole grapefruit or GFJ is associated with significant weight loss and improved insulin resistance in patients with metabolic syndrome, compared to placebo.…”
Section: Introductionmentioning
confidence: 78%
“…The findings from animal studies are promising, and relatively low-dose anthocyanin interventions with patients clinically diagnosed with vascular diseases have been associated with significant reductions in ischemia (34), blood pressure (2), and lipid levels (10). However, human intervention and clinical studies are limited, with the application of purified anthocyanins on endothelial function relative to other subclasses of polyphenols in tertiary prevention being relatively unknown (14).…”
Section: Discussionmentioning
confidence: 99%
“…Naringin, a polymethoxylated flavonoid commonly found in grapefruit, is another phytochemical that might have antimicrobial properties (Cvetnic and Vladimir-Knezevic, 2004). Research has mainly focused on its antioxidation (Jagetia et al, 2003), anticholesterol (Gorinstein et al, 2006), antiatherogenic (Choe et al, 2001) and osteogenic effects Rabie, 2006a, 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…Research focused on its antioxidant (Jagetia et al, 2003), anticholesterol (Gorinstein et al, 2005;Gorinstein et al, 2006) and antiatherogenic effect (Choe et al, 2001). It is a FDA (U.S. Food and Drug Administration) approved ingredient as an over-the-counter health supplement.…”
Section: Introductionmentioning
confidence: 99%